2009
DOI: 10.1007/s10562-009-0187-5
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Hydrogenations in Microemulsion Systems with Rh-TPPTS: Partial Hydrogenation of Sunflower Oil

Abstract: The effect of the P/Rh ratio and the surfactant concentration on the partial hydrogenation of sunflower oil in Triton X-100 microemulsion systems with the watersoluble catalyst complex Rh-TPPTS has been studied. An unusual hindering effect of the surfactant on the production of elaidic acid and stearic acid as the oil is hydrogenated was observed. When increasing the concentration of Triton X-100 in the reaction medium from 3 to 15 wt%, the content of elaidic acid and stearic acid were lowered 21 and 34%, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…There are examples in the past including, for example, hydrogenations. 95,96 The topic of reactions in microemulsion systems has been recently reviewed by Schwarze et al 97 The hydroformylation of long chain olefins with the help of surfactants has been under investigation within the last 15 years. 98 The group of Schomacker has been able to successfully develop a system for the hydroformylation of 1-dodecene in microemulsion media.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…There are examples in the past including, for example, hydrogenations. 95,96 The topic of reactions in microemulsion systems has been recently reviewed by Schwarze et al 97 The hydroformylation of long chain olefins with the help of surfactants has been under investigation within the last 15 years. 98 The group of Schomacker has been able to successfully develop a system for the hydroformylation of 1-dodecene in microemulsion media.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%
“…The hydrophilic catalyst remains in the water phase and can be reused. There are examples in the past including, for example, hydrogenations. , The topic of reactions in microemulsion systems has been recently reviewed by Schwarze et al…”
Section: Surfactant-based Systemsmentioning
confidence: 99%
“…Hamerla et al 36 showed that for the hydroformylation of 1-dodecene by Rh/SX higher reaction rates can be obtained when the reaction is performed in a triphasic microemulsion instead of W1 or W2 systems. Milano et al 35 studied the hydrogenation of sunflower oil and recycled the Rh/TPPTS catalyst up to three times by extracting the oil phase of a three-phase microemulsion system.…”
Section: Catalysis Science and Technology Minireviewmentioning
confidence: 99%
“…13 C NMR (DMSO-d 6 , 62.9 MHz): 14.3 (C 18 0 ), 23.6 (C 17 0 ), 25.9 (C 16 0 ), 27.9 (C 15 0 ), 30. 3, 30.4, 30.5, 30.6 (C 14 (1)(2)(3)(4)(5) were acetylated in the presence of acetic anhydride (12 equiv) and sodium acetate (1 equiv) for 24 to 72 h at 50 8C under stirring. The reaction was followed by TLC.…”
Section: 'mentioning
confidence: 99%
“…The use of transfer agents or surfactants, which are key compounds to the organized molecular systems can partially overcome these difficulties, while improving the catalytic activity [4]. Concerning hydrogenation processes, for example, the Rh-catalyzed hydrogenation of unsaturated substrates was one of the first widely described studies [5][6][7].…”
Section: Introductionmentioning
confidence: 99%